Optomechanical to mechanical entanglement transformation - Vacanti, G; Paternostro, M; Palma, G; Vedral, V (IOP Publishing, 2008)
We present a scheme for generating entanglement between two mechanical oscillators that have never interacted with each other by using an entanglement-swapping protocol. The system under study consists of a Michelson-Morley interferometer comprising mechanical systems embodied by two cantilevers. Each of them is coupled to a field mode via the radiation pressure mechanism. Entanglement between the two mechanical systems is set by measuring the output modes of the interferometer. We also propose a control mechanism for the amount of entanglement based on path-length difference between the two arms. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.